PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG DI KOPERASI BRIMOB POLDA JABAR JATINANGOR - Ririn Marliani; Kuwat Santoso (Jurnal Accounting Information System (AIMS), 2018)
The need for accurate and fast data processing on Koperasi inventory information system in Brimob Polda Jabar Jatinangor is needed in supporting business processes and reporting. Inventory management is still done manually and has not been done computerized. System design method that is SDLC (System Development Life Cycle) with the system design model used to help facilitate the development of the system, where each stage must be completed first before continuing the next phases. System design tools using Flow Map, Data Flow Diagram, Structure Chart, Data Dictionary and Entity Relationship Diagram.Koperasi inventory information system in Brimob Polda Jabar Jatinangor implemented with programming languages Microsoft Visual Studio 2010 and Microsoft Access 2010 database.Therefore, information on the supply of cooperative goods in Brimob Polda Jabar Jatinangor expected to assist the Koperasi in processing the data and the process of selling, purchasing, and credit payments.